A Novel Framework for Investigation of Cloud Attacks - Deevi Radha Rani , Nazma Sultana Shaik , Divya Vadlamudi, Sajja Radharani (International Journal of Advanced Science and Technology, 2020)
Cloud computing is a promising and computational intellectual technology intended to share storage, computation, and services evidently among substantial users. The use of cloud services introduces security and privacy risks. The centralized management system of cloud computing coupled with its magnitude, unprecedented openness, sharing and complexity can become a major target of hacker attacks making the security issues more severe than ever. The existing security mechanisms and tools cannot be applied to cloud computing environment which allows malicious insiders and criminals to exploit vulnerabilities of cloud architecture and perform various cloud attacks. This raise the necessity for investigation of cloud attacks. Some of the existing solutions allow investigation of cloud attacks but need to store huge traffic information in cloud for future investigation. In this paper, the proposed framework filters known malicious traffic and then exports traffic to cloud. The proposed framework ensures efficiency and reduced storage requirement.